An analysis of language style on Disney movie Mulan: 2020 - Salsa Billa Bulan Putri Effendi; Dona Rahayu Sugiharti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
People communicate with each other using their own style and characteristics to express their ideas and feelings. This research aims to analyze the types and dominant of use of language style in “Mulan: 2020” movie. This research used a descriptive qualitative method. The researcher used Martin Joos’s (1967) theory of language style. The researcher found 85 language style appeared in the “Mulan: 2020” movie which is divided into : Casual Style was found (19) times, Intimate Style (13) times, Consultative style (12) times, Frozen style (11) times, and Formal Style is the dominant language style in the movie